Abstract interpretation and optimising transformations for applicative programs - Mycroft, Alan (The University of Edinburgh, 1982)
This thesis describes methods for transforming applicative programs with the aim of improving their efficiency. The general justification for these techniques is presented via the concept of abstract interpretation. The work can be seen as providing mechanisms to optimise applicative programs for sequential von Neumann machines. The chapters address the following subjects. Chapter 1 gives an overview and gentle introduction to the following technical chapters. Chapter 2 gives an introduction to and motivation for the concept of abstract interpretation necessary for the detailed understanding of the rest of the work. It includes certain theoretical developments, of which I believe the most important is the incorporation of the concept of partial functions into our notion of abstract interpretation. This is done by associating non-standard denotations with functions just as denotational semantics gives the standard denotations. Chapter 3 gives an example of the ease with which we can talk about function objects within abstract interpretive schemes. It uses this to show how a simple language using call-by-need semantics can be augmented with a system that annotates places in a program at which call-by-value can be used without violating the call-by-need semantics. Chapter 4 extends the work of chapter 3 by showing that under some sequentiality restriction, the incorporation of call-by-value for call-by-need can be made complete in the sense that the resulting program will only possess strict functions except for the conditional. Chapter 5 is an attempt to apply the concepts of abstract interpretation to a completely different problem, that of incorporating destructive operators into an applicative program. We do this in order to increase the efficiency of implementation without violating the applicative semantics by introducing destructive operators into our language. Finally, chapter 6 contains a discussion of the implications of such techniques for real languages, and in particular presents arguments whereby applicative languages should be seen as whole systems and not merely the applicative subset of some larger language.
Keywords: sequential von Neumann machines.; abstract interpretive schemes.; call-by-need semantics.; destructive operators